The use of an antibiotic order form in a tertiary hospital: Influence on physicians' prescribing patterns. - Duc Chien Vo; Tuan Anh Mai; Thu Thao Nguyen; Dang Thoai Nguyen; Thi Ha Vo (GarVal Editorial Ltda., 2021)
Context: Vietnam is one of the countries at the high alert of antibiotic resistance. Aims: To evaluate the compliance rate and changes in physicians' prescribing patterns in patients with community-acquired pneumonia (CAP) before and after using the antibiotic order form (AOF) in a tertiary hospital. Methods: 120 inpatient medical records having antibiotic use and 115 patient medical records diagnosed with CAP at a Department of Respiratory Medicine during 3 months before and 3 months after using the AOF were retrospectively collected for assessment. Results: The compliance rate was 92%, and the average rate of filling in information fields was 58%. Comparison of prescribing behavior of CAP in control and intervention group showed that the rate of bacterial culture increased from 70% to 77% (p = 0.690), in which the rate of culture prior prescribing administration increased from 14% to 45% (p < 0.001), the initial antibiotic regimen with narrow-spectrum increased from 26% to 36% (p = 0.353), the proportion of patients improved clinically after 72 hours increased from 64% to 89% (p = 0.138), and the de-escalation decreased from 23% to 20% (p = 0.713). The treatment failure at hospital discharge decreased from 12% to 6% (p = 0.447). However, the length of treatment and the days of antibiotic treatment were not significantly different. Conclusions: The compliance rate was high, but the AOF filling rate was incomplete. Improving prescribing patterns and treatment efficacy in CAP patients is a suggestion to combine the AOF into multifaceted interventional efforts for specific patients.